Morbidity And Mortality Pattern In Bovine Of Himachal Pradesh - Singh, B.; Kumar , Sanjay (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
In the present study age, sex, season and cause wise morbidity and mortality data were collected from selected bovine owners of the Himachal Pradesh for a period of one year (January 2011 to December 2011). The reproductive diseases were more prominent having highest morbidity followed by specific diseases, parasitic diseases, digestive diseases, injury and accidents, nutritional deficiency, respiratory diseases and poisoning. Study of mortality pattern revealed that deaths occurred in bovine during study period were maximum due to poor management problems followed by digestive diseases, specific diseases, injury and accidents and for parasitic diseases. The calves were found at more risk of morbidity and mortality and the probability of getting disease reduces with increase in age.